A General Approach to Convert Hemicyanine Dyes into Highly Optimized Photoacoustic Scaffolds for Analyte Sensing. Issue 34 (1st July 2021) - Gardner, Sarah H.; Brady, Catharine J.; Keeton, Cameron; Yadav, Anuj K.; Mallojjala, Sharath C.; Lucero, Melissa Y.; Su, Shengzhang; Yu, Zhengxin; Hirschi, Jennifer S.; Mirica, Liviu M.; Chan, Jefferson
Abstract: Most photoacoustic (PA) imaging agents are based on the repurposing of existing fluorescent dye platforms that exhibit non‐optimal properties for PA applications. Herein, we introduce PA‐HD, a new dye scaffold optimized for PA probe development that features a 4.8‐fold increase in sensitivity and a red‐shift of the λabs from 690 nm to 745 nm to enable ratiometric imaging. Computational modeling was used to elucidate the origin of these enhanced properties. To demonstrate the generalizability of our remodeling efforts, we developed three probes for β‐galactosidase activity (PA‐HD‐Gal), nitroreductase activity (PA‐HD‐NTR), and H2 O2 (PA‐HD‐H2 O2 ). We generated two cancer models to evaluate PA‐HD‐Gal and PA‐HD‐NTR. We employed a murine model of Alzheimer's disease to test PA‐HD‐H2 O2 . There, we observed a PA signal increase at 735 nm of 1.79±0.20‐fold relative to background, indicating the presence of oxidative stress. These results were confirmed via ratiometric calibration, which was not possible using the parent HD platform. Abstract : We have developed PA‐HD, a new sulfur‐substituted dye platform exhibiting enhanced properties for photoacoustic probe development. To demonstrate generalizability, we employed PA‐HD to access probes for beta‐galactosidase and nitroreductase activities, as well as H2 O2 . Each probe was tested in live cells and in vivo. For instance, the H2 O2 probe was employed to visualize oxidative stress in an Alzheimer's disease model.